Analisis Sistem Pengendalian Internal Pemberian KUR pada PT Bank SUMUT Cabang Koordinator Medan - Putri Rahmadani; Yani Suryani; Iman Indrafana (Forum Kerjasama Pendidikan Tinggi, 2024)
This research was conducted by PT. Bank Sumut Medan Coordinating Branch is one of the government banks operating in the banking sector. The aim of the research is to analyze and find out whether PT. Bank Sumut has implemented an internalcontrol system correctly and on target in an effort to provide people's business credit to prospective debtors in accordance with the credit policies and procedures applicable in the company. This type of research is descriptive qualitative, the typeand source of research data is secondary data obtained from the company. Data collection techniques are documentation, observation and interviews, while data analysis techniques are qualitative descriptive. Based on the results of research conducted, it shows that PT. Bank Sumut Medan Coordinating Branch has implemented a good and smooth internal control system based on COSO principles, so that every credit given to a prospective debtor must meet the requirements and follow the applicable procedures of filling in complete and correct data using the form provided. PT. Bank Sumut also monitors all debtors who have received credit disbursement from the beginning of the credit agreement until the end of the credit term. The advice that can be conveyed is that for the future, leaders should provide more practical and sophisticated facilities for prospective debtors who wish to submit credit applications by filling them out digitally in accordance with current needs and technological developments so as to provide convenience and practicality for both parties.